The Effect of the Proportion of Female Directors and Independent Board of Commissioners on Financial Performance: Evidence from LQ-45 Companies on the Indonesia Stock Exchange 2022–2024 - Siska Dewi Wulandari; Lalu Hamdani Husnan (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study examines the influence of the proportion of female directors and independent board commissioners on corporate financial performance, measured by Return on Assets (ROA), among firms listed in the LQ-45 index on the Indonesia Stock Exchange (IDX) over the 2022–2024 period. Employing a quantitative causal design, purposive sampling yielded 30 companies across three fiscal years, producing 88 panel data observations sourced from annual reports via the IDX portal and Thomson Reuters Eikon Refinitiv. Panel data regression was conducted using a Random Effect Model (REM) estimated through Estimated Generalized Least Squares (EGLS) with cross-section weighting in STATA to address heteroscedasticity and autocorrelation. Empirical findings reveal that the proportion of female directors (PDP) exerted a positive and marginally significant effect on ROA (β = 535.4451, p = 0.1278) at the 90% confidence level, partially supporting H1. Conversely, the proportion of independent commissioners (DKI) demonstrated no statistically significant effect on ROA (β = −13,446.2347, p = 0.6812), attributable to negligible variability in DKI values across sample firms (SD = 0.0042) arising from homogeneous compliance with Financial Services Authority (OJK) regulatory thresholds, thereby rejecting H2. The model's R² of 3.30% indicates that predominant determinants of ROA reside beyond board compositional variables. Grounded in Resource Dependence Theory and Agency Theory, these findings underscore the strategic significance of directorial gender diversity for firm profitability in large capitalization Indonesian enterprises. Regulatory authorities are encouraged to institute more stringent gender diversity mandates, while future research should broaden the observation horizon and examine supplementary governance constructs.